Comparative proteomic analyses demonstrate enhanced interferon and STAT-1 activation in reovirus T3D-infected HeLa cells - Ezzati, Peyman; Komher, Krysten; Severini, Giulia; Coombs, Kevin M. (Frontiers in Cellular and Infection Microbiology, 2015)
As obligate intracellular parasites, viruses are exclusively and intimately dependent upon their host cells for replication. During replication viruses induce profound changes within cells, including: induction of signaling pathways, morphological changes, and cell death. Many such cellular perturbations have been analyzed at the transcriptomic level by gene arrays and recent efforts have begun to analyze cellular proteomic responses. We recently described comparative stable isotopic (SILAC) analyses of reovirus, strain type 3 Dearing (T3D)-infected HeLa cells. For the present study we employed the complementary labeling strategy of iTRAQ (isobaric tags for relative and absolute quantitation) to examine HeLa cell changes induced by T3D, another reovirus strain, type 1 Lang, and UV-inactivated T3D (UV-T3D). Triplicate replicates of cytosolic and nuclear fractions identified a total of 2375 proteins, of which 50, 57, and 46 were significantly up-regulated, and 37, 26 and 44 were significantly down-regulated by T1L, T3D and UV-T3D, respectively. Several pathways, most notably the Interferon signaling pathway and the EIF2 and ILK signaling pathways, were induced by virus infection. Western blots confirmed that cells were more strongly activated by live T3D as demonstrated by elevated levels of key proteins like STAT-1, ISG-15, IFIT-1, IFIT-3 and Mx1. This study expands our understanding of reovirus-induced host responses.